More Moments in Time: Images of Exemplary Nursing - Beth Perry (Athabasca University Press, 2009)
Within most disciplines, there are those who are recognized by their colleagues as being exceptionally competent practitioners. These individuals do their work in such a remarkable way as to become a model for others. This book is based on a study of the beliefs, actions, and interactions of a group of extraordinary oncology nurses-the people their peers would choose to have care for them if they were diagnosed with cancer. Perry's weaving of interviewee's stories and her own field notes and poetry creates a very personal perspective on nursing that leaves the reader with a greater understanding of the experience, and rewards, of caring for others.